1969
DOI: 10.1063/1.1671563
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectra and Geometry of SO2 Isotopes in Solid Krypton Matrices

Abstract: The infrared spectra of the 32S, 34S, 16O, 18O isotopic species of SO2 trapped in solid krypton matrices at 20°K are reported. Under conditions of medium resolution (∼0.8 cm−1), single bands are observed in each of the spectral regions which correspond to the three vibrational modes. Analysis of all the matrix data on the basis of a valence force field which includes anharmonic corrections and in which the bond angle is treated as a variable parameter yields force constants very close to those derivable from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
118
0
1

Year Published

1970
1970
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(131 citation statements)
references
References 21 publications
12
118
0
1
Order By: Relevance
“…[1,2,15] Therefore, it can be concluded from these IR data that the titanium isotope pattern is inconsistent with a bent species having a bond angle of less than 1608. The sine function is notoriously insensitive for linear and near-linear geometries.…”
Section: Methodsmentioning
confidence: 85%
“…[1,2,15] Therefore, it can be concluded from these IR data that the titanium isotope pattern is inconsistent with a bent species having a bond angle of less than 1608. The sine function is notoriously insensitive for linear and near-linear geometries.…”
Section: Methodsmentioning
confidence: 85%
“…Using the observed frequencies rather than the harmonic frequencies of the isotopomers inevitably leads to errors, but by making reasonable assumptions [36] it can be shown that substitution at X in XY 2 leads to a lower limit for the bond angle, while substitution at Y leads to an upper limit. The effects of anharmonicity can be appreciable, as is demonstrated for the diatomic molecule NiO isolated in argon matrices.…”
Section: Determination Of Bond Anglesmentioning
confidence: 98%
“…Vibrational spectra of OSO are well characterized in the gaseous phase 3,4 and in the matrix-isolated state. [5][6][7] Isomers of OSO have been the subject of numerous investigations for the last 40 years.…”
Section: Introductionmentioning
confidence: 99%